Application of mechanical surface treatments to improve fatigue crack growth life of aircraft fuselage materials - Liu, Yao (Cranfield University, 2018)
Mechanical treatment for surface processing is a cost-effective tool and has the potential to improve the dynamic strength of a component or structure significantly through creation of a residual compressive stress state. This research is aimed to investigate mechanical surface processing treatments, e.g. deep surface rolling, machine hammer peening, in aircraft fuselage structural alloys to reduce fatigue crack growth rate and improve damage tolerance. The study also revealed that such processing could be used effectively to improve damage tolerance properties of such safety critical structures. However, optimisation of such processes is important as distortion from the processing would need to be minimised, to maximise the benefit from the residual compressive stress field. This thesis focuses on the application of deep surface rolling to understand the underpinning interaction between stress states and a long fatigue crack under a variably distributed residual stress field. Centre notch of 8 mm length were machined in Middle-tension M(T) specimens of 1.6 mm thickness 2024-T351 and 2524-T351 clad aluminium alloys. The M(T) specimens were locally rolled by a deep surface rolling process to create a spatially resolved compressive residual stress fields on both sides of the notch and under different loads. Prior to application of deep surface rolling on the M(T) specimens, the process was trialled on similar thickness specimens to ensure minimum distortion so that it can be applied on both the surfaces. The spatial position of the DSR patches with respect to the crack tip were varied to understand the interaction of the stress field on crack propagation and how the benefit of the process can be maximised. Following rolling of M(T) specimens, fatigue testing were performed at a stress ratio R = 0.1 and maximum stress of 100 MPa. A three-dimensional finite-element (FE) model of the DSR process was developed to predict the residual stress field and distortion. This model was validated with experimentally measured residual stress data and distortion. An analytical method based on experimental residual stress data, was developed to determine the residual stress intensity factor (Kres). The crack closure behaviour was taken account for the prediction of the fatigue crack growth rate (FCGR). Despite formation of a compressive residual stress (CRS) field through the thickness below the DSR patch it was found that improvement of fatigue performance depends on the location of the patch with respect to the crack tip. It was observed that the rolling load parameters and distance from the crack tip are vital in the reduction of crack propagation behaviour. The former balances the stress field and distortion while the later determines the crack driving force, when the crack enters the compressive residual stress field, and a large distance between the crack tip and stress field will cause acceleration of the crack before it enters the compressive stress field. The analytical method of computing Kres was successfully contributed to the prediction of FCGR and showed good agreements with experiments. In a further study, the analytical method was used to calculate Kres by using the predicted residual stress field from FEA (finite element analysis). Based on the predicted Kres, the predicted FCGR showed a good agreement with experiments as well. The application of DSR to the metal fatigue enhancement is significantly effective and cost-effective. By optimising DSR process to intentionally treat the high possibility of fatigue damage region, the fatigue life can be significantly enhanced, resulting in improvement in damage tolerant design of aerospace structures or components.
PhD in Manufacturing
Keywords: Residual stress; deep surface rolling; stress intensity factor; finite element modelling; aluminium alloys; crack closure